Development of a southern hemisphere subtropical wetland (Welsby Lagoon, south-east Queensland, Australia) through the last glacial cycle. (15th December 2018) - Cadd, Haidee R.; Tibby, John; Barr, Cameron; Tyler, Jonathan; Unger, Lilian; Leng, Melanie J.; Marshall, Jonathan C.; McGregor, Glenn; Lewis, Richard; Arnold, Lee J.; Lewis, Tara; Baldock, Jeff
Abstract: Continuous records of terrestrial environmental and climatic variability that extend beyond the Last Glacial Maximum (LGM) in Australia are rare. Furthermore, where long records do exist, interpretations of climate and ecological change can be hampered by marked changes in sedimentary environment which, in turn, affect the taphonomy of palaeoecological remains. As a consequence, in order to determine how wetland systems responded to climatic and environmental changes, we first need to understand how their depositional environment changed through time. Here we document the development of freshwater Welsby Lagoon, south-east Queensland, from a 12.7 m sediment sequence with a basal age of ca. 130, 000 years. We present a variety of proxies reflecting change within the wetland. Carbon and nitrogen concentrations and carbon and nitrogen isotope ratios are used to infer the source of organic matter. However, the nitrogen limited nature of the catchment soils and presence of the colonial algae Botryococcus meant that organic material with C:N ≥ 20 is likely to be derived from autochthonous sources rather than terrestrial sources. A combination of photosynthetic pigments, plant macrofossils, aquatic pollen and sedimentary lignin was used to identify the sources of organic matter and the changing nature of this wetland. Since its formation, Welsby Lagoon has undergone a progressive change from an open-water, algae and cyanobacteria dominated, freshwater lacustrine system, to an aquatic macrophyte-dominated palustrine swamp after ca. 40 ka. It did not revert to lacustrine conditions during the Holocene, despite what is widely viewed as an increase in the regional moisture balance, most likely due to continual infilling of the wetland with sediment. With so few records of terrestrial change throughout MIS3 and MIS4, adequately understanding the development of sites like Welsby Lagoon is imperative to advancing our knowledge of this important environmental and cultural period in Australia's history, which encompasses events such as the extinction of megafauna and human colonisation of the continent. Highlights: First description of a new, continuous sedimentary record extending from MIS5 to present from sub-tropical Australia. An open water lacustrine environment dominated by aquatic algae and cyanobacteria occurred from approximately MIS5 to MIS2. A transition from a lacustrine to palustrine system occurred after ca. 40 ka. Aquatic macrophyte-dominated palustrine environment has persisted from 40 ka – present. Sediment pigments and plant macrofossils elucidate the source of sedimentary organic material.